Research of element composition of Verbena species - Nataliya M. Posatska; Оxana А. Struk; Andrii R. Grytsyk; Tetiana H. Stasiv; Anatolii O. Klymenko (Pensoft Publishers, 2021)
Violation of homeostasis is often connected with a deficiency or excess of certain elements. Undeniable value of biologically active substances of plants is that they are contained in plant raw material in natural balanced complexes and they are an important source of macro- and microelements for a human organism. Study of a chemical composition, including macro- and microelements, a pharmacological effect of Verbena species is a basis for conduction of further researches. There are 250 species of Verbena genus, 3 of which, namely Verbena officinalis L., Verbena supina L. and Verbena hybrida Hort are growing in Ukraine. The aim of our research was to study macro- and microelements in the raw material of Verbena genus species, to reveal the influence of the conditions of growing on the content of elements in the Verbena officinalis L. herb, to compare element composition of the Verbena officinalis L. herb and herbal extracts. Macro- and microelement composition of raw material was researched by using the method of atom-emission spectrometry with inductively bounded plasma iCAP 7000 Duo. To determine the influence of the conditions of increase of macro- and microelements in Verbena officinalis L. herb, their quantity in soils and plants from different areas of growing was defined. To reveal the intensity of absorption of macro- and microelements from the soil by the plants, the coefficients of their biological accumulation were calculated. The comparative determination of the element composition of Verbena officinalis L. herb and herbal extracts VOH-0 (extractant - purified water) and VOH-7 (extractant - 70% ethanol) was also carried out to determine the degree of elements transfer from plant raw material into extracts. Results of the research show that in the samples of Verbena officinalis L. herb, Verbena hybrida Hort. herb and Verbena supine L. leaves there are 22 inorganic elements. Results of studying of element composition of Verbena officinalis L. herb and samples of soil from different areas of growing in Ivano-Frankivsk and Ternopil regions show that the quantitative and qualitative compositions of microelements depend on element exchange of these plants, conditions of growing and element composition of soil. The reverse dependence between the content of most elements in the soil and the coefficient of their accumulation in plants was found out. Concentration of elements in the herb and extracts was identified to have the same profile, but the quantitative content of elements was different, which was influenced by the extractor (purified water, 70% ethanol). Results of our research are currently relevant; they should be taken into account in the development of new herbal medicines, which would have desirable pharmacological effect in the future.